Imagem-interface: o DVD e os novos formatos da comunicação digital - Garcia, Fabio Martinelli (2006)
The images (painting, photograph, cinema, etc.) had always been constructed for specific ends and through the mediation between us (spectators) and the reality, it was possible to represent the world that surrounded us. With the arrival of the graphical computation and new digital formats, the image acquires new abilities. To argue the properties and trends of the digital image are extremely excellent aspects for the development of new systems, processes and theories in communication. When it is conceived and allied to the interface concept, this image can be transformed into image-interface, thus multiplying, its characteristics and potentialities. A good platform to think the digital medias as inhabitable medias and the parameters to argue the transformation of the image in image interface is the digital video disc, because it possess technical characteristics witch allows the mapping of information and the storage of great amount of data. The objective of this research is to argue and apply the image-interface concepts, elaborated mainly by Peter Weibel, Lev Manovich and Mark Hansen, in the DVDs and the new formats of the digital communication like the Internet and electronic panels. The interfaces analysis of commercial and experimental DVDs and DVD Roms will allow to understand the current limitations in the interfaces´exploration and argue if it is possible to extend its resources and to use these concepts in the scope of a market culture, which a media quickly is substituted by another one before they deplete its possibilities